One-pot multicomponent green Hantzsch synthesis of 1,2-dihydropyridine derivatives with antiproliferative activity - Bosica, Giovanna; Demanuele, Kaylie; Padrón, José M.; Puerta, Adrián (Beilstein Journal of Organic Chemistry, 2020)
A rapid route for obtaining unsymmetrical 1,2-dihydropyridines (1,2-DHPs) as opposed to 1,4-dihydropyridines (1,4-DHPs) has been achieved via a one-pot multicomponent Hantzsch reaction. A benign protocol has been developed for the preparation of various 1,2-dihydropyridine derivatives using heterogenized phosphotungstic acid on alumina support (40 wt %). High yields of over 75% have been accomplished in just 2–3.5 h after screening several heterogeneous catalysts and investigating the optimal reaction conditions. The catalyst chosen has passed the heterogeneity test and was shown to have the potential of being reused for up to 8 consecutive cycles before having a significant loss in activity. In addition, aromatic aldehydes gave the aforementioned regioisomer while the classical 1,4-DHPs were obtained when carrying out the reaction using aliphatic aldehydes. The preliminary study of the antiproliferative activity against human solid tumor cells demonstrated that 1,2-DHPs could inhibit cancer cell growth in the low micromolar range.
Keywords: antiproliferative activity; 1,2-dihydropyridines; green Hantzsch synthesis; heterogeneous catalysis; one-pot multicomponent reaction